Malignant granular cell tumor in the thoracic wall: A case report - Gao, Shengnan; Xing, Bin; Lichao, Sun; Luo, Jie; Tang, Jiao; Wang, Ye; Zhang, Xiaoyan (Frontiers in Oncology, 2022)
Granulosa cell tumor (GCT) is a rare tumor that originates from neural/Schwann cells. GCTs can occur at any age and at any site in the body. The most common site is the tongue, followed by the mammary gland, upper respiratory tract ( throat and bronchus), and gastrointestinal tract (esophagus, large intestine and perianal area, stomach, small intestine, and bile duct). Malignant GCTs account for less than 1%–2% of all GCTs. Fewer than five GCTs in the thoracic wall have been reported, almost all of these benign. Here, we report a new case of malignant GCT of the thoracic wall, with rib invasion and pleural metastasis, in an Asian male. Microscopic examination revealed round, granular cells with eosinophilic cytoplasm and without prominent atypia. Despite these findings the disease showed rapid clinical progression. In summary, the tumor, although histologically ‘benign’, was clinically ‘malignant’.